Evaluation of Bank BSI Error Service Quality in Increasing Customer Satisfaction - M Mukhtar (West Science Journal Economic and Entrepreneurship, 2023)
This study aims to evaluate the quality of error services at Bank BSI and its impact on customer satisfaction. The method used in this study is a survey through questionnaires to Bank BSI customers who have experienced service errors in the last 6 months. Data collection will be carried out in May 2023 with a sample of 100 respondents. Data analysis uses descriptive statistical techniques and multiple linear regression. The results showed that the quality of Bank BSI's error services still needs to be improved, especially in terms of response speed and accuracy of solutions. In addition, service errors negatively affect customer satisfaction. Therefore, Bank BSI needs to make improvements and improve the quality of error services in order to increase customer satisfaction.